MATHEMATICAL BELIEFS IN SOLVING STATISTICS PROBLEMS: A CASE STUDY OF INTROVERTED STUDENTS AT A STATE ISLAMIC SENIOR HIGH SCHOOL - Elisa Setyaningrum; Pathuddin Pathuddin; Mubarik Mubarik; Rahma Nasir (Prima: Jurnal Pendidikan Matematika, 2026)
This study aims to describe the mathematical beliefs of an introverted student in solving statistics problems. The research was conducted at a State Islamic Senior High School in Palu City using a qualitative descriptive approach. The subject was a male student with an introverted personality and high mathematical ability, identified through the Eysenck Personality Inventory (EPI) and categorized as high-ability based on Arikunto’s classification. Data were collected through a statistics problem solving test and semi-structured interviews, then analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The findings, analyzed through five aspects of mathematical belief, indicate that the introverted student demonstrated positive mathematical beliefs throughout the statistical problem-solving process. He was able to understand problems thoroughly, plan steps systematically, carry out solutions independently and carefully, and review his answers reflectively. These five aspects were reflected in his beliefs about the importance of understanding problem, following solution steps, facing difficult problems, interpreting word problems, and persevering in effort. He relied more on independent thinking than social interaction, preferred structured and logical approaches, and was diligent in verifying his answers.